Metodologia para o ensino de cálculo para engenharia aplicado a mecânica e eletrostática - SILVA, Eliezer Tiago Sousa (2022)
The Differential and Integral Calculus is an indispensable discipline for engineering and related areas. This is fundamental to understanding physical effects, so it is necessary to be well understood its concepts and its importance for the courses of the area of exact and engineering. It is indispensable to understand the theoretical basis of the disciplines of calculation for a correct analysis and modeling of physical effects. In this article, we discuss how differential and integral calculus can be applied in engineering in an applied way, with examples focused on the study of motion and electrostatics.